A longitudinal pilot study of depressive symptoms in concussed and injured/nonconcussed National Collegiate Athletic Association Division I student-athletes - Roiger, T.; Weidauer, L.; Kern, B. (Journal of Athletic Training, 2015)
Context: Depression, which affects millions of Americans each year, among them collegiate student-athletes, can be caused by a wide range of circumstances, including sport-related injuries.